Common fixed point theorems in fuzzy metric‐like spaces employing common property (E.A.). (17th June 2019) - Sumalai, Phumin; Kumam, Poom; Gopal, Dhananjay; Hasan, Mohd
Abstract : The aim of this manuscript is to improve certain results established in a recent paper of Imdad et al on the existence of a common fixed point for contractive mappings in fuzzy metric spaces. Further, we generalize and extend some common fixed point theorems due to Ali and Imdad and some fixed point theorems due to Mihet to the case of fuzzy metric‐like spaces. We also furnish an illustrative example to demonstrate the validity of the hypotheses and degree of generality of our main result.